Comparison of flavonoid and policosanol profiles in Korean winter-spinach (Spinacia oleracea L.) cultivated in different regions. (1st May 2019) - Yuk, Heung Joo; Ryu, Hyung Won; Kim, Doo-Young; Park, Mi Hyeon; Seo, Woo Duck; Jeong, Seong Hun; Oh, Sei-Ryang
Highlights: Twenty flavonoids in spinach were tentatively identified by UPLC-QTof MS. Seven spinach flavonoids were evaluated by PLS-DA as key markers for quality control. The composition and content of policosanol in spinach was analyzed for the first time. Abstract: Spinach intake has long been highlighted globally because of its outstanding nutritional aspects. In this study, changes in flavonoids, a representative functional phytochemical group, were investigated by UPLC–QTof MS with multivariate analysis of winter-spinach samples from three different cultivation regions in Korea. From the partial least squares discriminant analysis (PLS-DA), the differences of flavonoids among the geographic locations were clearly distinguished. Seven spinach flavonoids (2, patuletin-3- O -glucosyl-(1 → 6)-glucoside; 4, spinacetin-3- O -glucosyl-(1 → 6)-[apiosyl-(1 → 2)]-glucoside; 8, patuletin 3- O -(2″-feruloylglucosyl)-(1 → 6)-[apiosyl-(1 → 2)]-glucoside; 11, spinacetin 3- O -(2″-feruloylglucosyl)-(1 → 6)-[apiosyl-(1 → 2)]-glucoside; 12, patuletin 3- O -(2′'-feruloylglucosyl)-(1 → 6)-glucoside; 18, 5, 3′, 4′-trihydroxy−3-methoxy-6:7-methylendioxyflavone-4′-glucuronide; 20, 5, 4′-dihydroxy-3, 3′-dimethoxy-6:7-methylendioxyflavone-4′-glucuronide) were evaluated as key markers among 20 isolated metabolites. Interestingly, the contents of individual marker were significantly different among the groups, though total amount of flavonoids were almost same. Additionally, policosanols (PCs) in the winter-spinach was examined quantitatively using GC–MS for the first time. The PCs were analyzed as the range of 53.6–59.2 mg/100 g, indicate that the winter-spinach is a beneficial source of PCs.